2016
DOI: 10.4269/ajtmh.15-0611
|View full text |Cite
|
Sign up to set email alerts
|

Successful Global Health Research Partnerships: What Makes Them Work?

Abstract: Abstract. There are many successful global health research partnerships, but little information is available about what makes them successful. We asked 14 research colleagues from Uganda, Kenya, and the United States who have extensive global health research experience about what they considered the top three factors that led to or impeded successful international research collaborations. Four key factors were identified: 1) mutual respect and benefit, 2) trust, 3) good communication, and 4) clear partner role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 4 publications
1
60
1
Order By: Relevance
“…However, such collaborations are beset with inequalities, given the economic disparities, power differentials and disparate research priorities between countries . Successful partnerships involve mutual respect, communication and clear partner roles between HIC and LMIC collaborators . Contrary to our hypothesis, our study showed that authorship parasitism was a relatively rare occurrence.…”
Section: Discussioncontrasting
confidence: 99%
“…However, such collaborations are beset with inequalities, given the economic disparities, power differentials and disparate research priorities between countries . Successful partnerships involve mutual respect, communication and clear partner roles between HIC and LMIC collaborators . Contrary to our hypothesis, our study showed that authorship parasitism was a relatively rare occurrence.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies demonstrate the importance of taking steps to minimize adverse outcomes to visiting providers, students, and trainees as well as to patients, communities, local providers, and health facilities in LMICs. 63,67,74 Also integral to the prevention of unintended adverse impact is the monitoring of true costs of the program to all institutions involved in the partnership. These include administrative costs for coordination of multiple partners, indirect impact on the community from exposure to short-term visitors, and ensuring appropriate reimbursement and steps to alleviate any undue burden.…”
Section: Prevention Of Adverse Impactmentioning
confidence: 99%
“…Programs reported innovative teaching opportunities, advanced training courses, and varied settings for patient care that were consistent with best practices for international partnerships. [25][26][27][28][29][30] Our study identified many opportunities for growth in the field of GH fellowship training such as improving interprofessional training, building partnerships with tribal councils, honing advocacy skills, and pairing fellows from high-resource and low-resource institutions. In the face of the rapid increase in GH fellowship programs and the common problems of funding and lack of qualified applicants, it is critical to continually reassess and prioritize needs of the international partners to ensure mutual benefit for all participants.…”
Section: Discussionmentioning
confidence: 99%